Risks of 5-100 Project: Perceptions of Academic Staff of Different Ages - I. G. Dezhina; G. Z. Efimova (Moscow Polytechnic University, 2022)
The implementation of the 5-100 Project in Russian universities, aimed at improving their competitiveness through adaptation to world standards and inclusion in the international educational environment has produced some quantitative and qualitative results. Despite the undoubted achievements of the universities participating in the Project, the mechanisms of its implementation have revealed some problematic areas that in the end can primarily affect the young generations of scholars. Therefore, assessing the perception of the 5-100 Project by scholars of different ages is important. The purpose of this article is to analyze, through the lens of a generational approach, the risks associated with the two aspects of universities' activities. First, the principles of funding under the 5-100 Project and second, the approaches applied for assessment of academic performance. The analysis is based on the results of semi-structured interviews with scientific and pedagogical staff at five universities that participated in the 5-100 Project (108 respondents). We analyzed the answers of respondents in three age groups: young scientists, middle-aged and older scholars. The study showed that there are areas where representatives of all generations are unanimous and areas where the young academics have perceptions different from other generations. There is unanimity in the attitudes to principles of financing practiced in the universities. The younger generation turned to be the most sensitive to insufficient spending on research equipment. In terms of performance evaluation indicators, the younger generation demonstrated the greatest adaptability to the system of formal quantitative assessment, while noting its dysfunctional effects. They have also revealed that it is easier for them to change jobs than for other generations of scholars.